Implementation Paper on Effective Way of Mobile Recharge - Sanodiya, Nitinkumar; Thawre, Vipul; Pohekar, Ankur; Gedam, Raju; Sarote, Kunal; Gawande, Dinesh (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
The title of our project is Smart Scan Recharge is android application which is able to do the recharge by just only scanning the recharge voucher. This application will also display the location of the recharge vender on GPS. This way of doing a recharge is very effective because it is very efficient than the manual process.